Extreme Neuroplasticity of Hippocampal CA1 Pyramidal Neurons in Hibernating Mammalian Species - Horowitz, John M.; Horwitz, Barbara A. (Frontiers in Neuroanatomy, 2019)
In awake and behaving mammals (with core and brain temperatures at ~37°C), hippocampal neurons have anatomical and physiological properties that support formation of memories. However, studies of hibernating mammalian species suggest that as hippocampal temperature falls to values below ~10°C, CA1 neurons lose their ability to generate long term potentiation (LTP), a basic form of neuroplasticity. That is, the persistent increase in CA3-CA1 synaptic strength following high-frequency stimulation of CA3 fibers (the hallmark of LTP generation at 37°C) is no longer observed at low brain temperatures although the neurons retain their ability to generate action potentials. In this review, we examine the relationship of LTP to recently observed CA1 structural changes in pyramidal neurons during the hibernation cycle, including the reversible formation of hyperphosphorylated tau. While CA1 neurons appear to be stripped of their ability to generate LTP at low temperatures, their ability to still generate action potentials is consistent with the longstanding proposal that they have projections to neural circuits controlling arousal state throughout the hibernation cycle. Recent anatomical studies significantly refine and extend previous studies of cellular plasticity and arousal state and suggest experiments that further delineate the mechanisms underlying the extreme plasticity of these CA1 neurons.